Precise computer models of the induction machine in the Matlab/Simulink - Shchur, Ihor; Rusek, Andrzej (NTU "KhPI", 2010)
Based on mathematical model of induction machine in orthogonal coordinate system, rotating with arbitrary angular speed, the computer model of this machine in software of Matlab/Simulink is built. The development of this model is relatively easy given the opportunity to consider in it the major deviations from the idealized: iron losses, saturation the main magnetic path and the paths of leakage magnetic flux, current displacement in squirrel-cage winding of rotor.